Reducing tax identity theft by identifying vulnerability points in the electronic tax filing process. (30th August 2021) - Ngugi, Benjamin K.; Hung, Kuo-Ting; Li, Yuanxiang John
Abstract : Purpose: Tax Identity Theft involves the illegal use of a potential taxpayer's identity, usually the social security number, to fraudulently file a tax return and claim a refund. The victim is the real owner of the social security number who will have difficulties getting a tax refund, as the offender has already taken a refund for the year in question. This paper aims to investigate whether the increased use and adoption of electronic tax filing (i.e. E-Filing) technologies has inadvertently resulted in a corresponding growth in Tax Identity Theft. Design/methodology/approach: Multiple regressions are used to analyze the data that is extracted from the Identity Theft complaint reports (maintained by the Federal Trade Commission) and the tax filing statistics (retrieved from the Internal Revenue Service). Findings: The results indicate that E-Filing can indirectly but significantly increase Tax Identity Theft through the full mediation effects of individual Self-E-Filing and Direct Deposit adoption, after controlling for general Identity Theft, the number of Individual Tax Returns and Total Refunds. Originality/value: The authors explore the association between the adoption of tax e-filing technologies and Tax Identity Theft. The findings suggest that the key loopholes in the Tax Identity Theft process are at the Self-E-Filing and the Direct Deposit points. Several practical recommendations for patching these loopholes are provided and discussed.